IN SEARCH OF EDUCATIONAL STRATEGY FOR UKRAINE - Ognevyuk, Viсtor (The Modern Higher Education Review, 2017)
The article deals with the world rating of Ukrainian educational sphere according to The Global Competitiveness Report and UNESCO Science Report. It shows comparative indices of Ukraine in contrast to the other countries of these world ratings according to the “Quality of primary education”, “Penetration of primary education”, “Penetration of secondary education”, “Quality of secondary education”, “Quality of education in Sciences”, “Quality of school management”, “School access to the internet” and others. The article also defines strategic directions of reforming Ukrainian education system to improve its position in the world  international ratings.